Regional Innovativeness Strategies And Their Impact On Innovativeness Of Provinces In Poland. A Spatio-temporal Analysis - Kowalik, Jan (Comparative Economic Research. Central and Eastern Europe, 2014)
Regional Innovation Strategies (RIS) have existed in Poland for almost ten years and in this period they have been developed, accepted and implemented in all provinces. The basic aim of Regional Innovativeness Strategies is to support regional or local authorities and other regional development organizations in defining and implementing an effective system of supporting innovativeness in the region. The current scope of realizing projects connected with RIS is different in particular provinces. The author of the paper attempts to evaluate the effects of implementation of pro-innovativeness solution included in Regional Innovation Strategies with particular consideration of their influence on the growth of region innovativeness level in Poland.